CRISPR/CAS9 mutagenesis of a single r-opsin gene blocks phototaxis in a marine larva. Issue 1904 (5th June 2019) - Neal, S.; de Jong, D. M.; Seaver, E. C.
Abstract : Many marine animals depend upon a larval phase of their life cycle to locate suitable habitat, and larvae use light detection to influence swimming behaviour and dispersal. Light detection is mediated by the opsin genes, which encode light-sensitive transmembrane proteins. Previous studies suggest that r-opsins in the eyes mediate locomotory behaviour in marine protostomes, but few have provided direct evidence through gene mutagenesis. Larvae of the marine annelid Capitella teleta have simple eyespots and are positively phototactic, although the molecular components that mediate this behaviour are unknown. Here, we characterize the spatio-temporal expression of the rhabdomeric opsin genes in C. teleta and show that a single rhabdomeric opsin gene, Ct-r-opsin1, is expressed in the larval photoreceptor cells. To investigate its function, Ct-r-opsin1 was disrupted using CRISPR/CAS9 mutagenesis. Polymerase chain reaction amplification and DNA sequencing demonstrated efficient editing of the Ct-r-opsin1 locus. In addition, the pattern of Ct-r-opsin1 expression in photoreceptor cells was altered. Notably, there was a significant decrease in larval phototaxis, although the eyespot photoreceptor cell and associated pigment cell formed normally and persisted in Ct-r-opsin1 -mutant animals. The loss of phototaxis owing to mutations in Ct-r-opsin1 is similar to that observed when the entire photoreceptor and pigment cell are deleted, demonstrating that a single r-opsin gene is sufficient to mediate phototaxis in C. teleta . These results establish the feasibility of gene editing in animals like C. teleta, and extend previous work on the development, evolution and function of the C. teleta visual system . Our study represents one example of disruption of animal behaviour by gene editing through CRISPR/CAS9 mutagenesis, and has broad implications for performing genome editing studies in a wide variety of other understudied animals.